Perilaku Remaja Putri Dalam Penggunaan Acne Cream Wajah Di Klinik Skin Care Kabupaten Banyuwangi - Pahlevi, Muhamad Gimnastiyar Reza; Supriyadi, Supriyadi; Hidayat , Cahya Tribagus (Riviera Publishing, 2025)
Introduction: Adolescence, with its physical and psychological changes, often triggers body image dissatisfaction and skin problems like acne, which drive the use of acne cream. AMC Clinic in Banyuwangi, with a large adolescent clientele, has seen an increase in demand for acne cream. Methods: This study is a quantitative research using a correlational method and a cross-sectional model. A sample of 58 respondents was selected through purposive sampling from a population of 68 respondents, collected through questionnaires, and analyzed using univariate (frequency) and bivariate (chi-square) analyses. Result: The study showed that the majority of respondents were aged 15-17 years (32.8%), had used acne cream for 1-3 months and 4-6 months (25.9%), and had good knowledge (94.8%), media access (87.9%), motivation (94.8%), and behavior in using acne cream (94.8%). Discussion: Knowledge, mass media usage, and motivation are significantly related to facial acne cream usage (Sig < 0.05). This study suggests that beauty clinics provide clear education about acne-prone skin care, adolescent girls are not easily influenced by advertisements and consult with experts, and further researchers examine other factors and the effectiveness of various acne creams.